Data Management in Biological Microscopy: A Librarian's Approach - Shuppy, Elliott (My University, 2015)
A growing demand for convenient sharing of research image data between the Laboratory for Optical and Computational Imaging (LOCI) and partner laboratories stimulated the need for enhanced data management processes and accompanying documentation. SLIS graduate student Elliott Shuppy began working with scientists as a researcher at LOCI in Fall 2014 to meet these current needs. During his talk he will discuss his involvement augmenting one scientist's data management workflow, including reflections on current practices, positioned and proposed tactics, and next steps in the process.